Ethical Practices in Facilitating Learning and Improving Educational Technology and Alternative Education by Using Google Classroom - Elihami Elihami; Ming Lin; Chang Biqing; Mai Ya (Edumaspul: Jurnal Pendidikan, 2023)
The globalization period has ushered in a race among nations to develop, adopt, and master new technology. Using technology in education is one of the most effective methods to do this. Utilizing education-based technologies, such as Google Classroom, can help Philippines Woman University (PWU) overcome the barriers to the adoption of online learning. Google Classroom has a distinct look and feel, like many new programs that emerge. Google Classroom is a component of the Google Apps for Education (GAFE) online suite of productivity tools for instructors and learners using the internet. This program offers a centralized location for interacting with students, offering feedback, and assigning assignments. Google Classroom has implications for how education is implemented in Philippines Woman University (PWU), including how teachers are evaluated, how students use technology, and more.